Measuring the message of Vaping’s Harm Exposure on Followers’ Attitudes and Intentions - Jesslyn Sihotang; Amanda Bunga Gracia; Rita Destiwati (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2026)
This study investigates the influence of exposure to vaping harm information, particularly through the TikTok account @geraldvincentt, on followers’ attitudes and their intention to not quit vaping. As e-cigarette use continues to rise among young adults, understanding how health messages on social media affect user behavior becomes increasingly important. Grounded in the Theory of Reasoned Action (TRA), this study explores whether exposure to negative health content can shape attitudes and reduce the intention to continue vaping. A quantitative approach was used, involving 400 respondents who follow @geraldvincentt. Data were collected using a Likert-scale questionnaire distributed via Google Form and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that exposure to vaping harm content significantly leads to more negative attitudes toward vaping and decreases the intention to continue its use. Furthermore, attitude mediates the relationship between information exposure and behavioral intention. The model demonstrates moderate explanatory power and predictive relevance. These findings suggest that while exposure to information alone may not immediately change behavior, shaping attitudes is a crucial step toward influencing behavioral intentions. This highlights the role of influencers like @geraldvincentt in strengthening public health messages through digital platforms.